An International Survey of Health Care Services Available to Patients With Tourette Syndrome - Bhikram, Tracy; Elmaghraby, Rana; Abi-Jaoude, Elia; Sandor, Paul (Frontiers in Psychiatry, 2021)
OBJECTIVE: Tourette syndrome (TS) is a neuropsychiatric disorder that is highly associated with several comorbidities. Given the complex and multifaceted nature of TS, the condition is managed by a wide variety of practitioners in different disciplines. The goal of this study was to investigate health service delivery and care practices by clinicians who see TS patients across different geographic settings internationally. METHODS: A comprehensive questionnaire was developed to assess clinical care resources for patients with TS and was sent to clinicians in Canada (CA), the United States (US), Europe (EU), and the United Kingdom (UK). Responses were compared quantitatively between geographic regions. RESULTS: The majority of respondents, regardless of region, reported that fewer than 40% of their case-load are patients with tics. The accessibility of TS services varied among regions, as indicated by differences in wait times, telemedicine offerings, comorbidity management and the availability of behavioral therapies. First-line pharmacotherapy preferences varied among physicians in different geographical regions with CA respondents preferring alpha-2-adrenergic agonists and respondents from the UK and EU preferring dopamine receptor antagonists. DISCUSSION: The results suggest that there is a scarcity of specialized TS clinics, potentially making access to services challenging, especially for patients newly diagnosed with TS. Differences in regional pharmacotherapeutic preferences are reflected in various published treatment guidelines in EU and North America. The lack of dedicated specialists and telemedicine availability, coupled with differences in comorbidity management, highlight the need for inter-professional care and holistic management to improve health care delivery to patients with TS.